Costs of scaling up health interventions : a systematic review - Johns, Benjamin (2005)
Presents a systematic review of the literature on the costs of scaling up health interventions. Identifies factors affecting costs as coverage increases. Describes typical cost curves for different kinds of interventions. Demonstarates that the costs of scaling up an intervention are specific to both the type of intervention and its particular setting.